Development of models for designing industrial energy technologies related to cold production and storage - Allet, Rémi (My University, 2011)
Numerous industries use cold fluids in their processes. Large energy savings can be achieved through the efficient use of technologies such as refrigerators and cold storage. However, their integration requires detailed studies to fit the network and the demand. A simulation tool is often an asset to estimate the performance of a system. The objective of this thesis is to develop models related to cold production and storage, allowing a user to assess systems’ design and performances through dynamic simulations. The work is based on the Modelica/Dymola environment. The Modelica language offers an innovative way to model systems by using equations instead of assignment statements. Due to this acausality, the same model can have multiple purposes. The technologies modelled are a refrigerator, a combined refrigerator/heat pump and a latent heat storage with spherical phase-change material (PCM) capsules. The refrigerator and the combined refrigerator/heat pump are an assembling of four components that are also modelled: a compressor, a condenser, an expansion valve, and an evaporator. The development followed strict rules that allow a user to include these components in a larger network with other systems. The performance of the models was assessed during test cases. They reveal a good accuracy of the results, from a theoretical and experimental point of view. Some difficulties were encountered, most of them due to the nature of the language or the way the refrigerant properties were retrieved for calculations. The models are however functional for most of the industrial studies. Applications for the developed models are various. They can be used to assess the performance of an existing or future network. They also authorize sensitivity analysis thanks to their easy-to-configure parameters. Finally, they are also suitable for designing equipment. One example in the thesis describes the combination of a refrigerator and a cold storage which adapt their production according to a cooling demand.
Keywords: Energi; Hållbar utveckling; Kemiska processer; Energy; Sustainable Development; Chemical Process Engineering